Sports and Chinese herbal medicine - ZeHua Yu; WenBin Wang; Kun Yang; JinFei Gou; Yi Jiang; ZhangBiao Yu (Elsevier, 2023)
Background: Chinese herbs have been used in sports and exercises as potent remedies for the treatment of sports injuries and recovery from sports fatigue. Herbs such as Astragalus, Radix Codonopsis, Shiitake and Rhodiola are favoured for their ability to help athletes improve their physical performance and to enable rapid recovery from fatigue. Abundant studies have proved that these traditional Chinese medicines(TCM) have a positive effect on athletic performance. For instance, TCM have been shown to have a significant recovery effect on skeletal muscle, cardiovascular and central nervous system fatigue caused by sports training or intense competition. Admittedly, it is necessary for more in-depth research to ensure the safety of TCM in sports. However, relatively little research has been done in this area and more studies are needed to assess and confirm the effects of TCM on the post-exercise organism, particularly with regard to the dosage of TCM, the duration of supplementation and a larger sample size. Purpose: The main purpose of the research is to restore athletes' athletic fatigue and improve their athletic performance through traditional Chinese medicine, changing the traditional massage method to restore fatigue. By looking for literature, the achievements of predecessors are summarized and summarized. Methods: I reviewed the literature of many scholars on Chinese medicine, described the value and potential of Chinese medicine in sports, and put forward a new research direction on Chinese medicine and sports Results: the results of scholars have shown that the fatigue recovery of athletes can be improved through traditional Chinese medicine, and the performance of athletes can be improved to a certain extent. Conclusion: The conclusion is that the conditioning through traditional Chinese medicine can promote the athletic performance of athletes, while improving their physiology and restoring fatigue to a certain extent.